Perceptions of holistic hypertension care among female community health workers and elderly women in rural Java, Indonesia - Rosiana Eva Rayanti; Aura Syafaroh; Ayu Afriani Panyuwa (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Hypertension management in rural Java currently focuses more on physical treatment and traditional herbal remedies, whereas a holistic care approach that integrates physical, psychological, social, cultural, and spiritual aspects is needed to be more effective, relevant, and sustainable. The lack of understanding of holistic care among cadres and older women has led to limited community involvement, so it is necessary to describe their perceptions to develop practical hypertension management appropriate to rural communities' needs. Purpose: To describe the perception of holistic care in hypertension management among female community health workers (locally known as cadres)  and older women in rural Java. Method: The research was conducted during integrated health development post activities and through home visits from July 2025 to February 2026 in a village in Semarang Regency, Central Java. The instruments used were Focus Group Discussion guidelines, semi-structured interview lists, and observation sheets. There were 22 Respondents, including 11 cadres and 11 older women, who met the inclusion criteria: being older adults cadres or older women with hypertension aged >60 years, being Javanese, and having a history of hypertension for >1 year. The exclusion criteria were elderly individuals with disabilities, bedridden individuals, and individuals unable to communicate. Data validity was ensured through triangulation of sources with community health Center nurses, midwives, and village heads. Results: The study revealed four themes: knowledge of the older women and cadres, health practices, dissemination of health information, and the roles of village midwives, elderly cadres, and families. Conclusion: This study found a limited understanding of holistic care among cadres and rural older women who still focus on the physical complaints of hypertension. Comprehensive education through midwives, cadres, families, and nurses is needed for optimal holistic management.